Seroprevalence of Mycobacterium avium subsp. paratuberculosis in Dairy Cattle in Khartoum State, Sudan - Wisal A. Elmagzoub; Nabawia M. Adam; Sanaa M. Idris; Mohamed E. Mukhtar; Sanaa A. Abdelaziz; Julius B. Okuni; Lonzy Ojok; Ahmed Abd El Wahed; ElSagad Eltayeb; Ahmed A. Gameel; Kamal H. Eltom (Veterinary Sciences, 2020)
Paratuberculosis, caused by Mycobacterium avium subspecies paratuberculosis (MAP), is a chronic wasting disease mainly of domestic and wild ruminants. It occurs worldwide, causing significant economic losses through decreased productivity, low fertility, increased cull rates and mortality. It is listed by the OIE (World Organization for Animal Health) as a disease of concern to trade in animals. Prevalence of this disease can be studied by detecting anti-MAP antibodies by Enzyme linked immunosorbent Assay (ELISA). The aim of this study was to investigate the current prevalence of MAP infection in cattle in Khartoum State. The overall apparent prevalence of MAP infection was found to be 6.3% and 18.9% at animal and herd levels, respectively. All seropositive animals were cross-bred females of good body condition; most of them (>90%) were >3 years old and >50% were from medium-sized herds in Omdurman. No significant association (p > 0.05) was found between seropositivity and animal herd size. The prevalence of MAP infection in Khartoum State is still low to medium compared to other parts of the world, but it is comparable to those reported from other African countries. Further studies with the view of designing nationwide surveys in domestic ruminants and camels in other states of the country are needed for establishing control programmes.